Generative AI and didactics: Nordic cases and implications for higher education: Editorial - Godsk, Mikkel; Christensen, Inger-Marie Falgren; Georgsen, Marianne (Tidsskriftet Læring og Medier (LOM), 2026)
This editorial introduces the 13 articles published in Læring og Medier (LOM) #31. Generative AI in Nordic higher education: cases and pedagogical implications. The didactic triangle is applied as an analytical lens to examine how GenAI affects teaching in the cases presented in this issue and, potentially, higher education more broadly. In this context, it is worth noting that the editorial uses the concept of ”didactics” in the Nordic-German sense, referring to the careful planning of teaching and learning activities. The editorial examines and explains how GenAI affects the relationships between educators, students, and subject matter (content), that is, the three original actors in the didactic triangle. In doing so, the editorial argues that GenAI does not merely function as an educational technology that can be described through the existing relationships and actors of the didactic triangle. Rather, GenAI should be incorporated as an active fourth actor in the triangle, positioning itself between the original three. Based on the cases provided in the issue, the three original relationships in the didactic triangle are analysed in the context of GenAI-mediation, including the identification of verbs that describe the relationships among the three original actors and GenAI. The editorial concludes that the challenge ahead is not whether to use GenAI, but how educators, students, and institutions can reclaim didactic agency by shaping the conditions under which GenAI can strengthen — rather than erode or short-circuit — meaningful relationships between educators, students, and content.